Microbiological analysis of mobile devices of surgical personnel working at a health care institution in Pereira, Colombia, 2018 - Acevedo-Osorio, German Oved; Gómez-Fernández, Adriana Marcela; Oyola-Leiva, Natalia; Arboleda-Angulo, Laura Daniela; Orozco-Cardona, Luisa María (Universidad y Salud, 2019)
Introduction: Cell phone use in hospital areas such as surgery rooms has become a common practice, which has increased both the risk of cross-contamination and the rates of surgical site infections. Objective: To determine microbial contamination of mobile devices belonging to surgical staff of a Health Care Institution in Pereira, Colombia during the first semester of 2018. Materials and methods: An observational, cross-sectional, descriptive study was conducted with a sample of ten mobile devices randomly chosen from health personnel working in the surgical room. Surface samples were collected from cell phone cases and bags using sterile swabs that were were kept in a 1% peptone salt solution until a deep plate count assay was performed on them. Results: The plate count confirmed the presence of mesophilic aerobes (93 CFUs), total coliforms (13 CFUs) as well as yeasts and molds (22 CFUs). Conclusion: The microbiological analysis showed elevated numbers of colony-forming units that could significantly increase the rates of infections associated with health care settings.